Cervical spondylotic radiculopathy - The role of conservative management - See, Lei Peng; Zakaria@Mohamad, Zamzuri; Karupiah, Rajandra Kumar; H.P., Marazuki (2018)
Cervical spondylotic radiculopathy is common and most patient experiencing an acute episode of unilateral radiculopathy without major motor deficit and no evidence of cord compression can be managed by non-operative measures.